Determinan Perilkau Oportunistik Penyusunan Anggaran(Studi Pada Kabupaten/ Kota di Provinsi JawaTimur) - Gumiadi, Aan; , Drs. Atwal Arifin,M.Si (2016)
This study aims to examine and analyze : Revenue , the influence of the remaining budget , Effect of General Allocation Fund against Opportunistic Behavior Composer Budget Regency / City in East Java province . The data used in this research is secondary data obtained from www.djpk.depkeu.go.id . The population in this study are all regencies / cities in East Java province in 2011- 2013 study period with the sampling technique used purposive sampling with criteria entire districts and cities that publish OPA years 2011- 2013 and report revenue budget data , Budget financing surplus and General Allocation Fund in 2011- 2013. Based on current criteria the number of samples have 86 District/City . The analytical tool used in this research is multiple linear regression . Based on the results of the analysis of this study show that the first hypothesis , local revenue ( PAD ) affects opportunistic behavior budgeting ( OPA ) . The results of the second hypothesis financing surplus budget ( Silpa ) effect on opportunistic behavior budgeting . Results of the third hypothesis general allocation fund has an effect on opportunistic behavior budgeting